1982
DOI: 10.1159/000166595
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular Hyperkalemia

Abstract: The literature regarding the various conditions associated with hyperkalemia and impaired tubular excretion of potassium is confusing. We propose a classification of these disorders based on clinical findings and, when possible, pathophysiology. We suggest the term ‘renal tubular hyperkalemia’ (RTH) to designate these conditions and define RTH as hyperkalemia disproportionate to any decrement in glomerular filtration rate and not due primarily or solely to mineralocorticoid deficiency or the effect of medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Dietary K + intake, which was not stated, may have been reduced and can have a marked effect on U K V in man 41 and animals. 42 As Perez et al 43 and Sanjad et al 11 point out, reduction of plasma K + with salt restriction does not rule out a defect in K + secretion.…”
Section: Hypertensionmentioning
confidence: 99%
“…Dietary K + intake, which was not stated, may have been reduced and can have a marked effect on U K V in man 41 and animals. 42 As Perez et al 43 and Sanjad et al 11 point out, reduction of plasma K + with salt restriction does not rule out a defect in K + secretion.…”
Section: Hypertensionmentioning
confidence: 99%
“…For this condition, the term 'renal tubular hyperkalemia' has recently been in troduced by Perez et al [9], They attributed this syn drome (which was also found in subjects with a normal glomerular filtration rate) to a tubular defect to excrete potassium in the presence of a high PAC. This descrip tion fits for 1 patient in the present study (No.…”
Section: Discussionmentioning
confidence: 99%
“…If reactivity to aldosterone were also increased in renal insufficiency, this might explain the poor relationship between the degree of renal failure and PAC [4], In some patients with renal insufficiency, renal potassium excretion can be increased by mineralocorticoid administration [6,7], but in others, tubular resistance has been reported [8,9]. No systematic com parative studies on the renal response to an excess of aldosterone in patients with renal insufficiency as com pared to normal subjects are available.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there were hyperchloremic metabolic acidosis with an apparently normal anion gap, even in the presence of monoclonal IgM, and hyporeninemic hypoaldosteronism. Perez et al [16] have recently proposed the term renal tubular hyperkalemia for the various conditions associated with hyperkalemia and impaired tubular ex cretion of potassium. According to their classification of renal tubular hyperkalemia, the present case is likely to belong to the group 111(b), i.e., a syndrome associated with mild to moderate renal insufficiency, decreased po tassium excretion, and low plasma aldosterone.…”
Section: Discussionmentioning
confidence: 99%